Different outcomes for transplant-eligible newly diagnosed multiple myeloma patients in Latin America according to the public versus private management: a GELAMM study. Issue 13 (9th November 2020) - Peña, Camila; Riva, Eloisa; Schutz, Natalia; Tarín-Arzaga, Luz; Martínez-Cordero, Humberto; Bove, Virginia; Osorio, Rocío; Chandía, Mauricio; Beltrán, Cecilia; Schulz, Javier; Cardemil, Daniela; Contreras, Carolina; et al.
Abstract: The aim of this study was to describe clinical and survival characteristics of transplant-eligible multiple myeloma (MM) patients in Latin America (LA), with a special focus on differences between public and private healthcare facilities. We included 1293 patients diagnosed between 2010 and 2018. A great disparity in outcomes and survival between both groups was observed. Late diagnosis and low access to adequate frontline therapy and ASCT in public institutions probably explain these differences. Patients treated with novel drug induction protocols, followed by autologous stem cell transplantation (ASCT) and maintenance, have similar overall survival compared to that published internationally.